Finding Meaning in Life for Human Flourishing and Wellbeing: A Mixed Method Research Exploring the Benefits, Possibilities and Challenges of the “On Our Journey” Cards (Journal of Advanced Research in Social Sciences, 2024)
The “On Our Journey” cards are an innovative resource and an accompaniment to live a happy life, helping individuals to identify, express and regulate their feelings, reflect, make healthy choices, validate their values/principles, and calibrate their life compass. The resource presents a process map where one can find meaning in one’s own actions and life and develop positive mental health which may not only change one’s life but create positive energy that will spread to people who play together with the “On Our Journey” cards, creating a sense of wellbeing and peace. The cards were developed by the Happy Life (Relationships are Forever Foundation) in Malta, together with a team of professionals. Through a set of questionnaires answered by participants who attended a three-day workshop training on the use of the “On Our Journey” cards, and a focus group with seven participants, four main themes emerged that explored the possibilities and the challenges of the cards. These are: the search for meaning in life and spirituality, positive mental health, wellbeing, and present-moment awareness. Results highlight the importance of understanding how to use the cards and the importance of being prepared for potentially challenging initial reactions. Mastery of card usage and allowing time to trust in their effectiveness can lead to significant improvements in human flourishing, mental health, well-being, spirituality, self-awareness, and meaning in life. This paper provides a valuable opportunity for educators and professionals to consider integrating the "On Our Journey" cards into their personal lives and professional practices.